Atuação do profissional de educação física na saúde do trabalhador em um hospital universitário - Gomes Tavares da Silva, Lidiane (2019)
There have been several transformations in the work environment and they have impacted the health of the worker. The hospital environment, recognized as an infectious-contagious and unhealthy environment, is also a place where there are professionals working with repetitive activities, prolonged use of the same positioning, exhaustive rhythm of work, including on-call duty, night shift, overload, productivity charge, accident risk, anti-allergic activities, and other working conditions that can cause several functional losses in the medium and long term. The Hospital implemented a Physical Exercise Program within the Worker's Health project, aimed at hospital employees, composed of periodic physical evaluation to monitor body composition and Pilates exercises and circuit to improve the quality of life and conducting scientific research in the interdisciplinary environment. This article is a report of experience to disseminate the interdisciplinary performance of the physical Education professional in a university hospital and the importance of the association of Professional Practice with science.